Trend 1998 - 2001. Statistics Canada. CANSIM: Manufacturing - Wood, Paper and Printing | Country: Canada | Province: Northwest Territories | Table: Logging industries, by North American Industry Classification System (NAICS) | Variable: Logging, Cost of fuel and electricity | Units: , 1998-2001. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 075-001-158. - Statistics Canada (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Statistics Canada (2015). CANSIM: Manufacturing - Wood, Paper and Printing | Country: Canada | Province: Northwest Territories | Table: Logging industries, by North American Industry Classification System (NAICS) | Variable: Logging, Cost of fuel and electricity | Units: , 1998-2001. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 075-001-158. Dataset: Provides statistics on Canadian manufacturers primarily engaged in making wood, pulp, paper, and paper products. Printing and related support activities are also included. CANSIM is Statistics Canada's key socioeconomic database. The datasets included here provide statistics on the Canadian population, and the nation’s resources, economy, society, and culture. In addition to conducting a Census every five years, approximately 350 active surveys are conducted on virtually all aspects of Canadian life. Statistics are provided for the nation as a whole, provinces, and other subnational geographies where available. Category: Industry, Business, and Commerce Source: Statistics Canada Established as Canada's central statistical office by the Statistics Act of 1985, Statistics Canada is required to "collect, compile, analyse, abstract and publish statistical information relating to the commercial, industrial, financial, social, economic and general activities and conditions of the people of Canada." Its main objectives are to provide statistical information and analysis about Canada’s economic and social structure and to promote sound statistical standards and practices. http://www.statcan.gc.ca/ Subject: Forestry and Wood Products Industry, Manufactured Goods, Manufacturing Businesses, Manufacturing Industry, Paper and Paper Products